Adverse Health Effects of the Long-Term Simultaneous Exposure to Arsenic and Particulate Matter in a Murine Model - Cesar Rivas-Santiago; Maria Gallegos-Bañuelos; Irving Trejo-Ramos; Nancy Solís-Torres; Raúl Quintana-Belmares; Noé Macías-Segura; Héctor Gutiérrez-Bañuelos; Lorena Troncoso-Vazquez; Bruno Rivas-Santiago; Irma Gonzalez-Curiel (Journal of Toxicology)
PM2.5 and arsenic are two of the most hazardous substances for humans that coexist worldwide. Independently, they might cause multiple organ damage. However, the combined effect of PM2.5 and arsenic has not been studied. Here, we used an animal model of simultaneous exposure to arsenic and PM2.5. Adult Wistar rats were exposed to PM2.5, As, or PM2.5 + As and their corresponding control groups. After 7, 14, and 28 days of exposure, the animals were euthanized and serum, lungs, kidneys, and hearts were collected. Analysis performed showed high levels of lung inflammation in all experimental groups, with an additive effect in the coexposed group. Besides, we observed cartilaginous metaplasia in the hearts of all exposed animals. The levels of creatine kinase, CK-MB, and lactate dehydrogenase increased in experimental groups. Tissue alterations might be related to oxidative stress through increased GPx and NADPH oxidase activity. The findings of this study suggest that exposure to arsenic, PM2.5, or coexposure induces high levels of oxidative stress, which might be associated with lung inflammation and heart damage. These findings highlight the importance of reducing exposure to these pollutants to protect human health.